2015
DOI: 10.1002/etc.3270
|View full text |Cite
|
Sign up to set email alerts
|

A fugacity-based toxicokinetic model for narcotic organic chemicals in fish

Abstract: A novel dynamic fugacity-based model is described, developed, and tested that simulates the uptake of narcotic organic chemicals in fish from water as occurs in aquatic bioconcentration and toxicity tests. The physiologically based toxicokinetic model treats the time course of chemical distribution in 4 compartments (tissue groups) in the fish, including the liver, in which biotransformation may occur. In addition to calculating bioconcentration and toxicokinetics, 5 possible toxic endpoints are defined corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Don and colleagues generated, collected, curated, and published databases of physical–chemical properties (Mackay et al, 2006); demonstrated relationships between solubilities and partition ratios; and developed methods for addressing the uncertainty inherent in measured and predicted chemical properties (Beyer et al, 2002; Cole & Mackay, 2000; Mackay, Bobra, et al, 1980; Shiu et al, 1988). Don repeatedly showed the principal relationships between partitioning properties and chemical activity with baseline toxicity (“narcosis”) in algae, invertebrates, fish, and mammals (Abernethy et al, 1986, 1988; Bobra et al, 1983, 1985; Celsie et al, 2016; Mackay et al, 2009, 2014; McCarty et al, 1992; Schmidt et al, 2018). He wrote and edited texts and numerous articles seeking to transfer this foundational knowledge to the research and regulatory communities (see Boethling & Mackay, 2000; Mackay, 1991; Thibodeaux & Mackay, 2010).…”
Section: Don Mackay Was a Master Of Simplifying Complex Conceptsmentioning
confidence: 99%
“…Don and colleagues generated, collected, curated, and published databases of physical–chemical properties (Mackay et al, 2006); demonstrated relationships between solubilities and partition ratios; and developed methods for addressing the uncertainty inherent in measured and predicted chemical properties (Beyer et al, 2002; Cole & Mackay, 2000; Mackay, Bobra, et al, 1980; Shiu et al, 1988). Don repeatedly showed the principal relationships between partitioning properties and chemical activity with baseline toxicity (“narcosis”) in algae, invertebrates, fish, and mammals (Abernethy et al, 1986, 1988; Bobra et al, 1983, 1985; Celsie et al, 2016; Mackay et al, 2009, 2014; McCarty et al, 1992; Schmidt et al, 2018). He wrote and edited texts and numerous articles seeking to transfer this foundational knowledge to the research and regulatory communities (see Boethling & Mackay, 2000; Mackay, 1991; Thibodeaux & Mackay, 2010).…”
Section: Don Mackay Was a Master Of Simplifying Complex Conceptsmentioning
confidence: 99%
“…For toxicokinetic and toxicodynamic or PBPK models in which uptake or effects in a target organ are evaluated it is essential to include that compartment explicitly. 17,27 An extreme example is the recent model by Larisch et al 28 that treats 10 internal organs and 3 external organs.…”
Section: Evolution Of Bio-uptake Modelsmentioning
confidence: 99%
“…26,27 Additionally, simplied partitioning rules can predict general pesticide distribution trends in mammal bodies; however, certain processes, such as metabolic rates in the liver, are oen omitted as part of conservative assumptions. 28 These modeling approaches, in addition to other bioaccumulation and PBK models, [29][30][31][32][33][34][35][36][37][38] have generally advanced our understanding of the fate of pesticides in animal bodies.…”
Section: Introductionmentioning
confidence: 99%